Mating-dependent lifespan cost of sterol depletion in male Drosophila melanogaster - Andrew W. McCracken; Nicola White; Jola Tanianis-Hughes; Elena Rosca; Thomas Gill; Libby McKinney; Stephen J. Simpson; Klaus Reinhardt; Marko Brankatschk; Matthew D. W. Piper; Juliano Morimoto; Stuart Wigby (Proceedings of the National Academy of Sciences, 2026)
Trade-offs between lifespan and reproduction are a central theme in evolution and ecology, often attributed to physiological constraints on the allocation of limiting resources. However, recent work suggests such trade-offs may depend on macro- and micronutritional context. We examined how macronutrient balance and cholesterol availability shape lifespan and reproductive performance in male Drosophila melanogaster , explicitly testing both unmated males and those permitted to mate freely throughout life—a design rarely applied. We found that cholesterol deprivation substantially reduced lifespan, but only in frequently mating males, indicating that sterols play a key role in mediating the lifespan costs of mating, consistent with their known role in sperm and seminal fluid. Conversely, the inclusion of dietary cholesterol reduced lifespan in unmated males maintained on low protein-to-carbohydrate diets, suggesting that male reproductive investment is sufficiently high to generate sterol-dependent costs to the soma. Lifespan was maximized at higher protein-to-carbohydrate ratios than previously estimated, while reproductive performance in aged males was favored by carbohydrate-biased diets, demonstrating a nutritional trade-off. Males preferentially consumed macronutrient ratios that promoted reproductive success rather than longevity and discriminated the presence of cholesterol in food. Together, these findings reveal sterols as a key mediator of male longevity, with effects that depend critically on both diet and reproductive context. More broadly, by integrating sterols, macronutrient balance, and sustained reproductive investment, our study adds to the growing evidence that male reproductive costs can be substantial and refines our understanding of the evolutionary basis of dietary trade-offs.